Fiduciary loyalty : protecting the due performance of non-fiduciary duties - Conaglen, Matthew (Bloomsbury collections, 2010)
Fiduciary Loyalty presents a comprehensive analysis of the nature and function of fiduciary duties. The concept of loyalty, which lies at the heart of fiduciary doctrine, is a form of protection which is designed to enhance the likelihood of due performance of non-fiduciary duties, by seeking to avoid influences or temptations that may distract the fiduciary from providing such proper performance. In developing this position, the book takes the novel approach of putting to one side the difficult question of when fiduciary duties arise in order to focus attention instead on what fiduciary dutie.